Edukasi Visual Melalui Plang Informasi: Upaya Peningkatan Kesadaran Masyarakat Tentang Lamanya Sampah Anorganik Terurai di Kelurahan Silea, Kecamatan Wundulako, Kabupaten Kolaka - La Ode Awal Sakti; Thareq R Ramadan; Nurul Yasmin Batrisya; Nur Aizah; Sinta Dewi; Vheny Suci Maulidah; Muhammad Fajri; Putri, Regina; Destari Putri Andargit; Heriani; Mahmud Albar; Riris Rismayanti; Rifka Yulia.N; Wemode Wasaungadi (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The problem of inorganic waste that is difficult to decompose poses a serious threat to environmental sustainability, both in rural and urban areas. Low public awareness of the long-term impacts of waste drives the need for simple, easy-to-understand educational strategies that directly involve residents. This community service activity aims to increase the understanding of residents of Silea Village, Wundulako District, Kolaka Regency, through visual information media that explains the length of time it takes for various types of waste to decompose. The implementation method begins with field observations to determine strategic installation points, followed by the design of information signs, the production process, and the installation stage with residents. The activity took place on August 8–10, 2025, involving 15 KKN students, village officials, and community groups. The number of participants involved in the socialization session was 45 people, consisting of housewives, youth from the youth organization, and representatives of the dasawisma (village). The results of the activity showed an increase in public understanding in differentiating between organic and inorganic waste, as well as awareness of the long-term impacts of accumulating plastic, cans, and glass waste. Active community participation in the sign installation process also fostered a sense of ownership, making the educational message more easily accepted. For housewives, the primary benefit was an understanding of daily household waste management, while for youth, this activity opened up insights into the importance of the younger generation's role in protecting the environment. In conclusion, the use of visual media in the form of information signs has proven to be an effective new approach to environmental literacy. This activity not only raises awareness but also strengthens community involvement, thus enabling more sustainable waste management.